Production of xylitol from sago trunk hydrolysate using Candida tropicalis - Mohamad, Nurul Lina (2011)
Xylitol is natural alternative sweetener and used in some foods because of a number of advantageous natural properties. Production of xylitol from agricultural waste, sago trunk cortex using Candida tropicalis was performed. Many researches have been carried out to increase the production of xylitol from various plant sources. Xylose, an intermediate carbon source for the xylitol production, was obtained from hemicellulose fraction of sago trunk cortex lignocellulosic compound. The diluted acid hydrolysis method was used to hydrolyze the xylose component. The influence of acid concentration and reaction time to obtain the optimum condition for xylose production was determined using Response Surface Methodology (RSM). It was found that xylose production was 22.78 g L-1 when operated with 8% sulfuric acid oncentration for 60 minutes reaction time. Results showed the formation of toxic compounds which are furfural and phenolic compound from hydrolysis process, inhibited the microorganism performance and subsequently reduced the product formation. Further improvement of xylitol production by Candida tropicalis was observed when using detoxification method. Detoxification of sago trunk hydrolysate was done using activated charcoal and overliming method. The activated charcoal method was found to be the best detoxification method with the highest xylitol concentrations were achieved when 2.5% (w/v) charcoal and adsorption time of 60 minutes was employed. In this condition, the xylitol concentration, volumetric productivity and yield were found 19.53 g L-1, 0.37 g L-1h-1, 0.78 g g-1, respectively. The fermentation conditions for Candida tropicalis were again obtained using RSM by varying the pH, temperature and agitation speed. The responses from RSM study for xylitol concentration, xylitol yield and volumetric productivity were found to be 19.23 g L-1, 0.79 g g-1 and 0.4 g L-1h-1, corresponding to the temperature of 34°C, pH 4 and agitation speed of 250 rpm. Based on the optimization parameter, an inoculum preparation was done in the sago trunk hydrolysate medium without adding nutrient in shake flasks. By performing the fermentation process in the bioreactor in attempt to further improve xylitol production by Candida tropicalis, it was found that the application of fermentation conditions has resulted in increased by 6% of xylitol concentration and 10% of volumetric productivity when compared to the results obtained under the shake flasks. The specific growth rate was found to be higher when fermentation was done in bioreactor compared to shake flasks. This indicating that the cell growth was favored by controlled conditions in the bioreactor than in the shake flasks.